OVERVIEW OF COMMUNITY STIGMA TOWARD PEOPLE LIVING WITH HIV/AIDS IN GORONTALO CITY - Nirwanto K. Rahim; Ita Sulistiani; Ayu Rofia Nurfadhilah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
HIV/AIDS remains a major public health concern worldwide, and stigma toward People Living with HIV/AIDS (PLWHA) continues to hinder prevention and treatment efforts, particularly in regions with limited health literacy. In Gorontalo City, community stigma persists due to misconceptions about HIV transmission, exaggerated fears, and culturally embedded moral judgments that associate HIV with deviant behavior. This study aims to describe the level of community stigma toward PLWHA in Liluwo Village and identify factors contributing to these attitudes. Using an analytical survey with a cross-sectional design, the study involved 185 respondents selected through stratified random sampling. A structured questionnaire assessed respondents’ HIV/AIDS knowledge, religiosity, and stigmatizing attitudes. The findings reveal that 102 respondents (55.1%) demonstrated stigmatizing behaviors, characterized by avoidance of physical contact, reluctance to live near PLWHA, fear of sharing public spaces, and inaccurate beliefs about how HIV is transmitted. Meanwhile, 83 respondents (44.9%) exhibited no stigma, showing higher levels of HIV-related knowledge, a better understanding of scientific facts about transmission, and a more empathetic and inclusive approach toward PLWHA. The variation between these groups highlights the crucial role of health literacy, cultural norms, and access to accurate information in shaping community attitudes. The study concludes that reducing stigma requires comprehensive and continuous educational interventions, targeted health promotion, and active involvement of community and religious leaders to build a more supportive environment for PLWHA. Strengthening public understanding is essential to ensure equitable treatment and improve the well-being of those affected by HIV.